Considerations on the Management of Urban Water Resources in Brazil:: an analysis of Ribeirão Vai-Vem in the Municipality of Ipameri (GO) (Élisée - Revista de Geografia da UEG, 2020)
This work aimed to present theoretical reflections on the management of urban water resources from the perspective of use ethics, and then analyze the situation of the Vai-Vem stream located in the urban area of Ipameri (GO). As a methodology for the realization, research was carried out: (i) theoretical, (ii) documentary and (iii) field, which allowed us to conclude that the lack of planning in Brazilian cities causes the deterioration of natural resources and the quality of life of the city. society. We found that the lack of treatment of urban sewage discharged into the bed of Vai-Vem compromises the water quality and the biodiversity of the stream.
Keywords: Water resources. Urban sewers. Vai-Vem stream.